2019
DOI: 10.1016/j.joca.2019.02.798
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of muscle activation and knee mechanics during gait between patients with non-traumatic and post-traumatic knee osteoarthritis

Abstract: Objective: The objective was to compare muscle activation and knee mechanics during gait between participants with non-traumatic knee osteoarthritis (OA), post-traumatic knee OA, and healthy adults. Design: Participants with non-traumatic knee OA (n ¼ 22), post-traumatic knee OA (n ¼ 19), and healthy adults (n ¼ 22) completed gait trials for this observational, cross-sectional study. Post-traumatic OA group had a history of traumatic anterior cruciate ligament (ACL) rupture. Surface electromyography (EMG) meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…In contrast, clinical progression was characterized by prolonged rectus femoris and lateral hamstring activity through mid-stance, describing a similar mechanism as Hatfield et al 19 of sustained coactivity of muscles contributing to worsening clinical symptoms. A cross-sectional study by Robbins et al 24 found non-traumatic OA patients displayed similar types of muscle co-contraction patterns to the clinical progression group, as compared to those with posttraumatic OA. Therefore, while the magnitude of loading appears to be important to structural disease progression, loading patterns and contributions from muscle are important considerations in reducing the burden of progression to advanced clinical symptoms, especially in non-traumatic OA.…”
Section: Biomechanics and Osteoarthritis Progressionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, clinical progression was characterized by prolonged rectus femoris and lateral hamstring activity through mid-stance, describing a similar mechanism as Hatfield et al 19 of sustained coactivity of muscles contributing to worsening clinical symptoms. A cross-sectional study by Robbins et al 24 found non-traumatic OA patients displayed similar types of muscle co-contraction patterns to the clinical progression group, as compared to those with posttraumatic OA. Therefore, while the magnitude of loading appears to be important to structural disease progression, loading patterns and contributions from muscle are important considerations in reducing the burden of progression to advanced clinical symptoms, especially in non-traumatic OA.…”
Section: Biomechanics and Osteoarthritis Progressionmentioning
confidence: 98%
“…The assessment of muscle activation patterns through EMG remains an important method in understanding the etiology and progression of OA 71 , and the past year saw number of important findings in this area 19,21,24 , including advancements in using EMG in musculoskeletal force modeling 72e74 . Diamond et al 72 used EMG and marker trajectories with patient-specific neuromuscular modelling to estimate and compare hip joint contact forces in individuals with hip OA and controls.…”
Section: Electromyography Modellingmentioning
confidence: 99%
“…Exclusion criteria included knee trauma or surgery within the last 12 months, history of joint arthroplasty in the lower extremities, neurological conditions (e.g., previous stroke), severe cardiovascular conditions (e.g., angina pectoris), or any other conditions affecting gait. Participants were part of an ongoing longitudinal study, 21,23 and all available participants were analyzed for the current study. Participants provided written, informed consent before enrollment.…”
Section: Participantsmentioning
confidence: 99%
“…However, biomechanical and clinical studies have shown increased joint load and articular cartilage degeneration after knee meniscus resection [ 4 ]. A study by Robbins et al demonstrated differences between OA subtypes with respect to the disease characteristics that may impact disease progression [ 5 ]. Another study reported approximately 25–50% lower risk of medical consultation for knee OA after meniscus repair as compared to arthroscopic partial meniscectomy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%